Meningkatkan Kemampuan Membaca Permulaan Anak Lambat Belajar Melalui Bimbingan Belajar Permainan Dadu Huruf - Bahrul Dwi Cahyadi; Alfin Miftahul Khairi (Program Studi Bimbingan dan Konseling, 2023)
Early reading is one aspect and initial foundation for children to be able to understand and grasp letters and words. This research aims to improve the early reading skills of slow learners in special schools through guidance and counseling in learning the dice game. The type of research used is Classroom Action Research. The sample for this research was children who were identified as slow learners, namely 3 children in class 2 of SDLB. The treatment used is a letter dice game. Research was carried out at the pre-cycle, cycle I, cycle II and cycle III stages. Each cycle consists of planning, action, observation, and reflection. The data analysis used is descriptive quantitative percentage. The results of this research are that in the pre-cycle the reading ability of slow learners is still very low. In the pre-cycle, the percentages of the three slow learners were 26%, 22% and 18%. Then it increased in cycle I after receiving treatment, the percentages became 36%, 32% and 32%. In cycle II, initial reading ability increased again with the percentages of the three children 39%, 40% and 44%. And in cycle III there was a significant increase in the three children, namely 54%, 61% and 64%. The conclusion from the classroom action research that the researchers conducted was that learning with the dice letter game was able to improve the early reading skills of slow learners.